Determinant Factors Of Contraceptive Method Choice In Central Java (Analysis Of 2017 IDHS Data) - Wibowo, Syifa Sofia (International Journal of Health Literacy and Science, 2025)
The variable contributing to an increase in the maternal mortality rate (MMR) is 4T, which stands for too old, too young, too near, and too many. By using contraceptives, the family planning program may be able to avoid 33% of MMR if it is properly run. The goal of this study is to identify the determinants (mother’s age, level of education, economic status, number of children, site of living, and health insurance) that affect women's decision to use contraceptives, particularly in Central Java. This observational study, which employed data from the 2017 IDHS, was conducted. Cross-sectional data collection and Pearson product-moment bivariate test. The research sample was taken from the study population using the total sampling, a total of 3,645 data. The study's findings indicate that there is a relationship between a mother's age, education level, type of home, ownership of health insurance, and the form of contraception she chooses for herself and her children in the Central Java Province. Economic position is the one that has the most influence, and health insurance ownership is the factor that has the least impact.